CDR 2019
DOI: 10.20517/cdr.2019.57
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of nuclear factor erythroid 2-related factor 2 in the mechanism of action and resistance to anticancer therapies

Abstract: Nuclear factor E2-related factor 2 (NRF2), a transcription factor, is a master regulator of an array of genes related to oxidative and electrophilic stress that promote and maintain redox homeostasis. NRF2 function is well studied in in vitro, animal and general physiology models. However, emerging data has uncovered novel functionality of this transcription factor in human diseases such as cancer, autism, anxiety disorders and diabetes. A key finding in these emerging roles has been its constitutive upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 242 publications
(342 reference statements)
1
4
0
Order By: Relevance
“…Our data show that NIH1-induced Nrf2 nuclear translocation is correlated with an increase of Nrf2 mRNA levels. This is consistent with data showing that, once in the nucleus, Nrf2 binds the antioxidant response element (ARE) sequences and induces its own expression via a positive feedback [ 55 , 56 ]. Moreover, the binding of Nrf2 to ARE also causes the transcription of phase II antioxidant enzymes, including HO-1 and NQO1 [ 57 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our data show that NIH1-induced Nrf2 nuclear translocation is correlated with an increase of Nrf2 mRNA levels. This is consistent with data showing that, once in the nucleus, Nrf2 binds the antioxidant response element (ARE) sequences and induces its own expression via a positive feedback [ 55 , 56 ]. Moreover, the binding of Nrf2 to ARE also causes the transcription of phase II antioxidant enzymes, including HO-1 and NQO1 [ 57 ].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, EBEO increases the levels of other natural antioxidants in the body, such as SOD and CAT which protect the liver from PAR-induced hepatotoxicity ( El-Banna et al., 2013 ). The mechanisms postulated to BEO as antioxidants including (1) scavenging of ROS; (2) chelation of iron which initiates radical reactions and inhibition of enzymes responsible for the generation of ROS ( Edenharder and Gruñhage, 2003 ); (3) antioxidants can interfere with xenobiotic-metabolizing enzymes, block activated mutagens/carcinogens, modulate DNA repair and even regulate gene expression ( Paramasivan et al., 2019 ). All these mechanisms may be important for their antimutagenic and anticarcinogenic properties ( De Flora and Ferguson, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it should be noted that the Nrf2 blocker that we used in these studies, ML385, does not interfere with Nrf2 nuclear translocation, but blocks Nrf2 transcriptional activity by interfering with binding of Nrf2 to the ARE in the promoter region of Nrf2 target genes [ 33 ]. On the other hand, it has been reported that Nrf2 binding to ARE not only promotes antioxidant gene expression, but also triggers a positive feedback loop leading to further Nrf2 expression [ 34 , 35 ]. Therefore, our immunofluorescence observations, summarized in Figure 5 , may reflect the fact that OS results both in increased Nrf2 nuclear translocation and in increased Nrf2 expression, while treatment with ML385 inhibits Nrf2-triggered Nrf2 expression, thereby reducing significantly the amount of Nrf2 that may translocate to the nucleus.…”
Section: Discussionmentioning
confidence: 99%